Bio-sourced novel monomers and polymers for plastics sustainability - Alshehri, Norah (2025)
This thesis details the synthesis of several novel monomers from biomass chemicals such as terpenes and furfural. Several synthesis routes were explored to produce a broad spectrum of functional groups suitable for polymerisation, such as hydroxyls, carboxy acids, epoxides, lactones, and methacrylate. In chapter two, terpene-derived monomers were synthesised via the derivatisation of -pinene, -pinene, limonene and geraniol. This resulted in novel monomers with diols, hydroxy-carboxylic acids, di-carboxy acids and epoxides. In chapter three, a six-membered ring lactone monomer was synthesised from furfural. Some of these monomers have been used in synthesising sustainable polyesters and polymethacrylate, which contain a unique cyclohexane ring or a double bond in their backbone, making them suitable for post-polymerisation modification. The functionalisation of limonene, -pinene, -pinene and geraniol has enabled the synthesis of several renewably-sourced monomers to form terpene-derived polyesters. Step growth homo-polymerisation of diols, diacids and hydroxy-acid yields low molecular weights of novel polyesters. The limonene diol derivatives are demonstrated to function as co-monomers alongside a renewable diacid. The resultant polyesters display Mns of up to 8400 g/mol. -Pinene was used to synthesise dialcohols, which served as co-monomers with a renewable diacid, enabling the synthesis of two novel polyesters.